2009
DOI: 10.2478/s11536-009-0054-1
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s disease: the most common diagnostic mistakes in Lithuania

Abstract: AbstractParkinson’s disease (PD) belongs to group of neurodegenerative diseases. PD diagnosis is clinical, based on these signs: tremor, rigidity, bradykinesia, akinesia or hypokinesia. The aim of the work was to determine the frequency of separate clinical forms of Parkinson’s disease and difficulties at this disease diagnosis. After examining 267 patients, foreseen clinical criterion of Parkinson’s disease correspond 202 (44.0% persons) − 115 women and 87 men and for 65 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…It was found that before physical therapy the worst quality of life was found in mobility and daily living activities. Results of our research coincide with the study carried out by V. Valeikienė et al (2009) which showed that the worst quality of life among patients with Parkinson's disease was found in mobility and daily living activities.…”
Section: Discussionsupporting
confidence: 87%
“…It was found that before physical therapy the worst quality of life was found in mobility and daily living activities. Results of our research coincide with the study carried out by V. Valeikienė et al (2009) which showed that the worst quality of life among patients with Parkinson's disease was found in mobility and daily living activities.…”
Section: Discussionsupporting
confidence: 87%
“…Also, prior to the research, the participants were informed about anonymity of the research and that they could withdraw from it at any time, that the participation was Therefore we could not compare results. Parkinson's disease is the second most common chronic neurodegenerative disease after Alzheimer disease (Valeikienė et al, 2004). During the disease, a lesion in basal ganglia, especially substantianigra, starts to develop.…”
Section: Methodsmentioning
confidence: 99%